France’s experience with monetary and exchange rate management: March 1973 to end-1981 - V. ARGY (PSL Quarterly Review, 2013)
The work encompasses a detailed review of the French experience with regards to monetary and exchange rate management. Monetary and credit targeting is dealt with and the instruments used to achieve proximate policy objectives are reviewed. Economic activity and inflation are then assessed before a simple econometric analysis of the Franc-Dollar rate is performed. Finally, France’s experience with policy mixes and internal-external balance is explored.